2010
DOI: 10.1097/bpo.0b013e3181df1578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Results of Lateral Condylar Fracture of Distal Humerus in Children

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 20 publications
4
46
0
Order By: Relevance
“…In these cases, the rate of deep infection is approximately 0.2% while that for superficial infection is 0.8% 6 . The infection rate of lateral condyle fractures has been noted to be higher (8.1%) but in the study by Koh et al it is not clear what proportion of K-wires were buried 7 . Some studies have directly compared buried and non-buried wires in lateral condyle fractures but no significant difference in outcome or complications was shown between the two groups 8 …”
Section: Discussionmentioning
confidence: 95%
“…In these cases, the rate of deep infection is approximately 0.2% while that for superficial infection is 0.8% 6 . The infection rate of lateral condyle fractures has been noted to be higher (8.1%) but in the study by Koh et al it is not clear what proportion of K-wires were buried 7 . Some studies have directly compared buried and non-buried wires in lateral condyle fractures but no significant difference in outcome or complications was shown between the two groups 8 …”
Section: Discussionmentioning
confidence: 95%
“…Bony overgrowth (lateral spurring) over the lateral condyle is a distinct radiological finding commonly seen in children following a fracture of the lateral condyle of the humerus [12, 18]. A recent study by Pribaz et al [19] consisting of 212 lateral condyle fractures treated by various methods, demonstrated that 73 % of the patients developed some degree of lateral spur.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Although closed reduction for displaced fractures remains controversial, recent studies have shown promising results. [12][13][14][15] Compression is important in these small, articular fractures, and the optimal mode of fixation for maintaining fracture reduction is debated. 14-17 Several constructs (eg, multiple smooth pins, single lag screw, and threaded pins) have been described.…”
mentioning
confidence: 99%